School's out Forever: Postsecondary Educational Trajectories of Students with Autism. (August 2016) - Karola, Dillenburger; Julie‐Ann, Jordan; Lyn, McKerr
Abstract : Objective: Postsecondary educational attainment is the key for successful transition to adulthood, economic self‐sufficiency, and good mental and physical health. Method: Secondary analyses of school leavers' data were carried out to establish postsecondary educational trajectories of students on the autism spectrum in the United Kingdom. Results: Findings show that students with autism who had attended mainstream secondary schools enter Further Education (post‐16 vocational training) at lower rates and Higher Education (University) institutions at a similar rate to other students. They study the full range of subjects on offer. However, they are more likely to be younger, study at a lower academic level, and remain living at home with their parents. Conclusion: While course completion data were not yet available, attainment data showed that prospects are improving, although more needs to be done to enable these young adults to achieve their full postsecondary educational potential.